Investigation of in-vitro cytotoxic and antibacterial activity of methanol extract of Crotalaria verrucosa leaves - Nowrin, Tasnova (BRAC Univeristy, 2017)
This project report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2016.